The lived experience of pain-related fear in people with chronic low back pain - Bunzli, S.; Smith, Anne; Schütze, R.; O'Sullivan, P. (2017)
Low back pain (LBP) is a leading cause of disability worldwide. One of the strongest predictors of LBP disability is pain-related fear. The fear avoidance model (FAM) describes how the belief that pain signals damage to the spine can lead individuals into a cycle of fear and avoidance, which in turn sustain pain and physical and psychosocial disability. A large body of research has supported the relationships proposed by the FAM; however, randomized controlled trials based on the model have reported modest effect sizes for reductions in fear and disability. Limitations of the model in its current form may be impeding its clinical utility and applicability to the wider population of people with LBP and high pain-related fear. In particular, while the FAM conceptualises pain-related fear as a "phobia" driven by the underlying belief that pain signals damage, it is possible that "non-phobic" processes also trigger pain-related fear and avoidance. In this chapter, we examine the lived experience of LBP and pain-related fear. We explore personal explanations and narratives related to the beliefs underlying pain-related fear, the factors associated with these beliefs and how fear may change over time. We consider how individual variance in qualitative data relates to scores on quantitative measures of fear. Finally, we offer an alternative framework to understand the lived experience of pain-related fear, based on "common sense" rather than only "phobic" processes. We will propose that incorporating a "common sense" perspective into future iterations of the FAM may extend its clinical utility and have implications for the next generation of fear avoidance research.